Encyclopedia of Industrial Biotechnology 2009
DOI: 10.1002/9780470054581.eib013
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins

Abstract: Aflatoxins are toxic and carcinogenic secondary metabolites produced primarily by the filamentous fungi Aspergillus flavus and Aspergillus parasiticus . Aflatoxin biosynthesis is a complex process involving many intermediates and enzymes, which are regulated at multiple levels. Owing to its complexity and importance, scientists from biochemistry, molecular biology and genetics are attracted to the study of its mechanisms of biosynthesis and regulation. These effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 196 publications
0
3
0
Order By: Relevance
“…Later, a completed aflatoxin pathway gene cluster was established when a 75 kb DNA sequence was determined (Yu et al 2004a-c). Based on genome sequence data, this aflatoxin gene cluster is located on chromosome III near subtelomeric region (Yu et al 2008(Yu et al , 2010a. The primary evolutionary advantage of gene clustering may be for the purpose of coordinated gene expression.…”
Section: Aflatoxin Biosynthetic Pathway Gene Clustermentioning
confidence: 99%
“…Later, a completed aflatoxin pathway gene cluster was established when a 75 kb DNA sequence was determined (Yu et al 2004a-c). Based on genome sequence data, this aflatoxin gene cluster is located on chromosome III near subtelomeric region (Yu et al 2008(Yu et al , 2010a. The primary evolutionary advantage of gene clustering may be for the purpose of coordinated gene expression.…”
Section: Aflatoxin Biosynthetic Pathway Gene Clustermentioning
confidence: 99%
“…In the absence of veA ,aflatoxins (AFs), the highly toxic hydrophobic secondary metabolites produced by some Aspergillus species [8], are not produced. Null mutants of laeA also are unable to produce AFs and other secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that conidiophore development and secondary metabolism are co-regulated [ 4 , 5 , 6 , 7 ]. In the absence of veA ,aflatoxins (AFs), the highly toxic hydrophobic secondary metabolites produced by some Aspergillus species [ 8 ], are not produced. Null mutants of laeA also are unable to produce AFs and other secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%